2011
DOI: 10.1186/1471-2202-12-89
|View full text |Cite
|
Sign up to set email alerts
|

The somatostatinergic system in the mammalian cochlea

Abstract: BackgroundLittle is known about expression and function of the somatostatinergic system in the mammalian cochlea. We have previously shown that somatostatin administration may have a protective effect on gentamicin-induced hair cell loss. In this study, we have analyzed the cochlear expression of somatostatin receptor 1 (SST1) and somatostatin receptor 2 (SST2) at both the mRNA and the protein level in wild-type mice, as well as in SST1 and SST2 knock-out (KO) mice and in cultivated neurosensory cells.ResultsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
(31 reference statements)
4
13
0
Order By: Relevance
“…In addition, it is noteworthy that the developmental pattern of SSTR1 and SSTR2 expression are similar. In our previous publication we observed that deletion of one receptor subtype was compensated by an overexpression of the other receptor subtype [25]. These findings support the idea that both receptors have a related function in the inner ear.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, it is noteworthy that the developmental pattern of SSTR1 and SSTR2 expression are similar. In our previous publication we observed that deletion of one receptor subtype was compensated by an overexpression of the other receptor subtype [25]. These findings support the idea that both receptors have a related function in the inner ear.…”
Section: Discussionsupporting
confidence: 76%
“…Our previous study demonstrated that SSTR1 and SSTR2 mRNA and protein were expressed in the adult mouse cochlea, and were localized in the IHC, outer hair cells (OHC), and supporting cells of the OC [25]. SSTR3, 4, and 5 have not been shown to be essential for the function of SST [10].…”
Section: Introductionmentioning
confidence: 99%
“…SSTR2 protein was strongly expressed in DeC, and to a lesser extent in OHC, but was absent from PiC and IHC compared with WT mice. In SSTR2 KO the staining pattern did not differ from that of WT mice [30]. In addition, no major compensatory regulation of SST or individual SSTRs has been described as a consequence of the genetic deletion of SSTR1 or SSTR2 in specific brain regions [37].…”
Section: Expression Of Somatostatin Receptors In Cochlea Of Knock Outmentioning
confidence: 88%
“…In the retina, recently major alterations of SST content were demonstrated as a consequence of SSTR1 or SSTR2 deletion [38]. Indeed, SSTR1 loss causes an increased expression of SSTR2 [30]. In the DKO mouse cochlea the expression of SSTR3 mRNA, as measured with quantitative qPCR in OC explants from P21 day-old mice was not significantly changed but the expression of SSTR4 in OC explants from P21 day-old mice was significantly decreased compared to age matched OC explants from WT mice.…”
Section: Expression Of Somatostatin Receptors In Cochlea Of Knock Outmentioning
confidence: 99%
See 1 more Smart Citation